Fiscal Revenue, Inflationary Finance and Growth - Choudhry, Nurun (IMF Working Papers; Working Paper, 1992)
This paper analyzes the optimal rate of monetary expansion when government resorts to inflationary finance to generate additional investment for enhancing growth. If there are lags in tax collection, an increase in inflation erodes real fiscal revenue, thereby worsening the current balance while reducing government investment. This impedes capital accumulation as well as increases the welfare cost of inflation. As such, the optimal rate of monetary expansion, equilibrium capital-labor ratio and output are lower while the marginal cost of inflationary finance is higher than they would be without collection lags. Simulations are performed to highlight empirical implications.